Synthesis a Number of Heterocyclic Compounds and some of chalcones Derived From Levofloxacin - Ekram Abdullah Basheer; Kalid Matny Al-jaanaby; Feras Shauki Al-joboury (Tikrit Journal of Pure Science)
The hydrazide (1) was used as synthone for the following Compound pyridazine-3,6-dione (2) by reaction of hydrazide (1) with maleic  anhydride and Compound phthalazine-1,4-dione (3) by the reaction of  hydrazide (1) with phthalic anhydride. Substituted thiosemicarbazides (6-7) by hydrazide(1) reaction with substituted isothiocyanates in ethanol. The thiosemicarbazide (5) was, also synthesized by the reaction of hydrazide (1) with ammonium thiocyanate in presence of concentrated hydrochloric acid. 1-Formyl-2-acyl hydrazine (4) was obtained by the reaction hydrazide (1) with formic acid, and Substituted 1,3,4-oxadiazoles (8-12) were obtained by reaction the hydrazide (1) with substituted carboxylic acid. Then, it was cyclized by phosphorous oxy chloride. 1,3,4-Oxadiazole-5-thiol (35) was synthesized by reaction of  the  hydrazide (1) with carbon disulfide in presence alcoholic potassium hydroxide solution. Then, the compound (35) was used to synthesize: a- 1,3,4-Oxadiazoles (36-39) by reaction with alkyl halide. b-1,3,4-Oxadiazoline thione (40) by reaction with formaldehyde.  c- Triazole (41) by reaction with hydrazine hydrate in absolute ethanol. Pyrazolines compounds (23-32) were synthesized from the reaction of the hydrazide (1) with chalcones (13-22) (which were prepared by condensation of substituted  Benzaldehyde with substituted acetophenone under basic conditions). Pyrazoline dion (33) and pyrazole (34) were synthesized through the reaction of the hydrazide (1) with diethyl malonate and acetyl acetone respectively.